Facing up to the human variome project: analysis on the adequacy of Malaysian laws in dealing with the legal challenges arising / Haniwarda Yaakob - Yaakob, Haniwarda (2014)
Malaysia is now a member of the international Human Variome Project (HVP), a project initiated to collect and share genetic data obtained worldwide that cause human diseases. In this regard, Malaysia has established the Malaysia Human Genome Variation Consortium known as the 1Malaysia Human Genome Variation Consortium (1Mhgvc) to act as the Malaysian node for the HVP. The 1Mhgvc has initiated steps to collect genetic data from Malaysians with the aim to finding genetic data that cause diseases such as thalassemia, cancers and other genetic disorders. While this project will help revolutionise the healthcare industry in Malaysia by saving lives and reducing medical costs, its arrival is not without ethical and legal concerns. The possibility of genetic discrimination and the issue of individual privacy cannot be undermined when genetic data from individuals are gathered for this purpose. Law, therefore, must be able to keep abreast with this advancement by providing adequate tools to safeguard the interests of individuals concerned and society at large. This forms the crux of this paper where two main issues arising from the Human Variome Project namely, genetic discrimination and individual privacy will be critically analysed. It will be determined whether the existing laws in Malaysia are sufficient to address these possible concerns. In doing so, laws from other jurisdictions will be examined and used as a benchmark in proposing for new laws and policies (if necessary) to be adopted within Malaysian legal framework.